Thrombolytic and Antimicrobial Activities of Andrographis paniculata ? A Preliminary Investigation: Thrombolytic and Antimicrobial Activities of Andrographis paniculata - Al-Amin, Md. Mamun; Nasir Uddin, Mir Muhammad; Islam, Md. Siddiqul; Chowdhury, Muhammad Ibrahim; Shohel, Mohammad (Biological Sciences - PJSIR, 2014)